Get Over Yourself : Nietzsche for Our Times. - West, Patrick (Societas., 2017)
Many books have sought to introduce the writings of the infamous and influential philosopher, Friedrich Nietzsche, but Get Over Yourself puts matters the other way round. Rather than simply explaining his thought, it instead asks: what would Nietzsche make of us? What would he think of our 21st-century, digital age? In our time of identity politics, therapy culture, 'safe spaces', religious fundamentalism, virtue-signalling, Twitterstorms, public emoting, 'dumbing-down', digital addiction and the politics of envy, the book introduces Nietzsche by putting the man in our shoes. Get Over Yourself.